Biotoxicity of essential oil of Eucalyptus citriodora Hook (Myrtaceae) to dust mites - Cai, Haiming; Xie, Pusong; Zhang, Xu; Lin, Zhibin; Xu, Zhimin; Chen, Shuting; Ruan, Peiyao; Akutse, Komivi S.; Li, Shanshan; Lin, Huiquan; Wu, Ziyi; Lin, Yongwen (Frontiers in Plant Science, 2025)
IntroductionDust mites are a prevalent indoor allergen contributing to respiratory diseases like allergic rhinitis and asthma. Eucalyptus citriodora essential oil, known for its balsamic odor and repellent effects on various pests, has been scantily investigated for its impacts on dust mites.MethodsThe chemical composition of the essential oil and its head-space extracted from E. citriodora was determined using gas chromatography-mass spectrometry (GC-MS). The toxicity of the oil and its compounds were assessed through contact-fumigant and vapor-phase mortality bioassays. Repellent effects were evaluated using a fabric-contact assay. Data were analyzed using probit regression to determine LC50 values.ResultsThe essential oil contained seven main compounds, and citronellal, citronellol and citronellyl acetate were the most abundant in the oil's volatile, accounting fora total of 88.22%. Citronellal exhibited the highest toxicity, and the essential oil itself showed strong toxicity with the LC50 of 63.94 and 84.53 μL/cm against Dermatophagoides pteronyssinus, 60.72 and 75.88 μL/cm against Dermatophagoides farinae, respectively. In vapor-phase assays, citronellal and ethyl phenylacetate caused 100% mortality.DiscussionCitronellol had the highest repellent effect, and the essential oil, 1,8-cineole, and citronellyl acetate also showed significant repellency rates. E. citriodora essential oil and its compounds particularly citronellal and citronellol, showed high potential for effective dust mite control due to their natural origin, strong toxicity and repellency impacts. Thus, E. citriodora essential oil is a natural, eco-friendly alternative to synthetic acaricides, providing a scientific basis for the control of indoor dust mite allergies.